The Scope of Area Studies in the Era of Globalization - Kiran, Sobia (International Journal of Humanities and Education Development (IJHED), 2022)
Area Studies has always been approached ambivalently since its political birth after the Second World War. Despite a quiet acknowledgement of the contribution of Area Studies in the production of knowledge from the local lens to correct the ‘universal’ Western perspective of the knowledge produced by social sciences, questions are raised about its very existence in the era of globalization. This paper addresses the problematic of the marginalized position of Area Studies. The discussion will include; i) articles by Arif Dirlik, Ravi Arvind Palat, Tessa Morris-Suzuki to address the problematic of marginalization of Area Studies; ii) the articles by Edward Said, Aijaz Ahmad, Dispeh Chakrabrty, Vivek Chibber, and Kuan-Hsing Chen to assess the limits of Postcolonialism and Marxism in deconstructing Eurocentrism of Area Studies; and finally iii) the scholarly debates by Asef Bayat, David Ludden, Neil Smith, Naoki Sakai, Christian von Soest, and Alexander Stroh to discuss the utility of comparative method as a bridge to ford the rifts between Area Studies and social sciences. It is necessary to broaden the scope of Area Studies by engaging in cross-regional as much as cross-disciplinary research with the social sciences and other disciplines which are trying to meet the demands of transnational pressures generated by the global capitalism. The selected scholars highlight the need to revise Area Studies by proposing new approaches to free it from Eurocentrism and to make it more interdisciplinary to meet the demands of globalization